Diabetes and cognitive outcomes in a nationally representative sample: the National Health and Aging Trends Study. (October 2014) - Wennberg, Alexandra M. V.; Gottesman, Rebecca F.; Kaufmann, Christopher N.; Albert, Marilyn S.; Chen-Edinboro, Lenis P.; Rebok, George W.; Kasper, Judith D.; Spira, Adam P.
ABSTRACT Background: The prevalence of both type II diabetes mellitus (DM) and cognitive impairment is high and increasing in older adults. We examined the extent to which DM diagnosis was associated with poorer cognitive performance and dementia diagnosis in a population-based cohort of US older adults. Methods: We studied 7, 606 participants in the National Health and Aging Trends Study, a nationally representative cohort of Medicare beneficiaries aged 65 years and older. DM and dementia diagnosis were based on self-report from participants or proxy respondents, and participants completed a word-list memory test, the Clock Drawing Test, and gave a subjective assessment of their own memory. Results: In unadjusted analyses, self-reported DM diagnosis was associated with poorer immediate and delayed word recall, worse performance on the Clock Drawing Test, and poorer self-rated memory. After adjusting for demographic characteristics, body mass index, depression and anxiety symptoms, and medical conditions, DM was associated with poorer immediate and delayed word recall and poorer self-rated memory, but not with the Clock Drawing Test performance or self-reported dementia diagnosis. After excluding participants with a history of stroke, DM diagnosis was associated with poorer immediate and delayed word recall and the Clock Drawing Test performance, and poorer self-rated memory, but not with self-reported dementia diagnosis. Conclusions: In this recent representative sample of older Medicare enrollees, self-reported DM was associated with poorer cognitive test performance. Findings provide further support for DM as a potential risk factor for poor cognitive outcomes. Studies are needed that investigate whether DM treatment prevents cognitive decline.